Can political rhetoric ever be "too persuasive"? : The combination of proverb and hyperbole in the case of having the cake and eating it - Musolff, Andreas (Array, 2020)
Can the use of linguistic devices to achieve persuasion, such as metaphor, irony and hyperbole, ever be “too persuasive”, i.e., overshoot its rhetorical aim? More specifically, can the combination of such devices be “too much of a good thing” in that it commits speakers (and approving hearers) to actions that they were not part of their persuasion intentions? This paper investigates the semantic and pragmatic development of the Brexit-related applications of the metaphorical proverb, You cannot have your cake and eat it, during 2016–2019 in British public discourse. At the start of that period, the proverb’s reversal into the assertion “We can have our cake and eat it!” by the then Foreign Secretary Boris Johnson and other “Brexiteers” became a highly prominent endorsement of Brexit and its supposed benefits for the UK; it even temporarily set the agenda for the public perception of UK–EU negotiations. Over time it became an object of hyperbolic praise as well as derision and recently seems to have lost much of its persuasive force. The paper argues that the proverb’s new reversed application by Johnson was initially successful in reviving its metaphorical meaning and framing it in a hyperbolic rhetorical context but that it also pushed Brexit proponents to an “all-or-nothing” outcome of the conflict narrative, both vis-à-vis the EU and within the British political debate. Thus, rhetorical success can lead to argumentative (and political) commitments that may have been not foreseen by the speaker and may run counter to their persuasive interests.